AISYAH BINTI ABU BAKAR INSPIRASI BAGI AKTIVIS PERJUANGKAN KESETARAAN GENDER DAN INKLUSI SOSIAL PEREMPUAN - khusnia rahmawati; Nicky Estu Putu Muchtar (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
The article entitled 'Aisyah Binti Abu Bakar Inspiration for Activists to Fight for Gender Equality and Women's Social Inclusion, represents the writer's anxiety. At least as follows; First, women cannot fully accept their existence if they hold positions as heads of agencies or institutions, whether owned by the government or private. Second, women are seen by some people as second-class human beings after men, so that their existence is often belittled and belittled. Third, women are seen as the property of men, so that their existence is under the control of men and seems underappreciated. Fourth, women's social environment is also limited, both in terms of places and people. For a number of concerns as described by the author above, it is an attraction and concern for conducting a study with a literature approach. While the method used is library research, which is qualitative in nature. While the results to be achieved from this study are; First, it can explore the reasons why women experience not being fully accepted as leaders, the reasons why women are seen as second-class human beings after men, the reasons women are seen as the property of men, the reasons women's association is limited. Second, it can reveal the issues and strategies of activists in the struggle for gender equality and women's social inclusion. Third, reveal the aspects contained in 'Aisyah Binti Abu Bakar which can be used as inspiration for the movement for gender equality and women's social inclusion. Finally came to a conclusion; First, that there are a number of reasons why women experience rejection as leaders, are seen as second-class human beings, their existence is the property of men, their association is restricted. Second, there are issues at play, including strategies in fighting for gender equality and women's social inclusion. Third, that 'Aisyah Binti Abu Bakar can be used as a model and inspiration for the movement for gender equality and women's social inclusion.